Physiological Responses to Hypoxia on Triglyceride Levels - Morin, Renée; Goulet, Nicholas; Mauger, Jean-François; Imbeault, Pascal (Frontiers in Physiology, 2021)
Hypoxia is a condition during which the body or specific tissues are deprived of oxygen. This phenomenon can occur in response to exposure to hypoxic environmental conditions such as high-altitude, or because of pathophysiological conditions such as obstructive sleep apnea. Circumstances such as these can restrict supply or increase consumption of oxygen, leading to oxyhemoglobin desaturation and tissue hypoxia. In certain cases, hypoxia may lead to severe health consequences such as an increased risk of developing cardiovascular diseases and type 2 diabetes. A potential explanation for the link between hypoxia and an increased risk of developing cardiovascular diseases lies in the disturbing effect of hypoxia on circulating blood lipids, specifically its capacity to increase plasma triglyceride concentrations. Increased circulating triglyceride levels result from the production of triglyceride-rich lipoproteins, such as very-low-density lipoproteins and chylomicrons, exceeding their clearance rate. Considerable research in murine models reports that hypoxia may have detrimental effects on several aspects of triglyceride metabolism. However, in humans, the mechanisms underlying the disturbing effect of hypoxia on triglyceride levels remain unclear. In this mini-review, we outline the available evidence on the physiological responses to hypoxia and their impact on circulating triglyceride levels. We also discuss mechanisms by which hypoxia affects various organs involved in the metabolism of triglyceride-rich lipoproteins. This information will benefit scientists and clinicians interested in the mechanistic of the regulatory cascade responsible for the response to hypoxia and how this response could lead to a deteriorated lipid profile and an increased risk of developing hypoxia-related health consequences.